Some Approaches to the Analysis of a Group of Repeated Measurements Experiment on Mahogany Tree with Heteroscedustic Model - Islam, Md Nasirul; Rouf, Abu Syeed Md Ripon; Rahman, M Mazibar (Journal of Agriculture & Rural Development, 2008)
Combined analysis of a group of repeated measurements experiments could play an important role in both the causes either the variance might be known or unknown. Ordinarily the variances vary from experiment to experiment depending on places and environmental conditions due to great irreconcilable inherent causes. On the other hand the variances are obviously related as a functional form of the respective error variances in different places. Relying on the functional form some tests criterion are proposed for removing any resulting bias. Key words: Repeated measurements experiments, divergency and convergency, percentage rotatability.